PPPUD INDUSTRI BATIK PODHEK DI KABUPATEN PAMEKASAN PROVINSI JAWA TIMUR - Baidawi, Muhammad; Rahayu, Yayuk Ngesti; Harmadji, Dwi Ekasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The aim of the Regional Superior Product Development Program(PPPUD) in the third year is to improve the marketing of the Podhek Pamekasan batik. Marketing of Podhek batik is still focused on offline marketing. In marketing craftsmen compete unhealthily. Craftsmen have not yet realized the importance of IPR. The method of implementing community service uses the mentoring method. The results of the PPPUD implementation, as follows, form the pilot of the podhek batik center, optimize work programs from joint business groups, improve packaging, exhibit batik, offline and online batik marketing, include craftsmen in the dissemination of the importance of patents, patent the podhek batik products, publish at seminars national, scientific publications in the mass media, strengthening of craftsmen in terms of batik motif design, cooperation with Australian batik entrepreneurs, and assistance during the visit of the regent's mother and guests. Podhek batik craftsmen have no problems in the production and design of podhek batik motifs. Craftsmen need support from all parties, both from their own craftsmen, entrepreneurs and local governments in terms of marketing. They must continue to innovate. Batik craftsmen need to be educated about the importance of cooperation between craftsmen between entrepreneurs and the government in marketing batik podhek so that batik prices can be stable so that the market can also be stable. In terms of marketing and shipping goods abroad it needs to be facilitated or facilitated so that batik exports can be maximally increased.